2019
DOI: 10.3389/fneur.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Recurrence, and Risk Factors for Peri-ictal Central Apnea and Sudden Unexpected Death in Epilepsy

Abstract: Introduction: Peri-ictal breathing dysfunction was proposed as a potential mechanism for SUDEP. We examined the incidence and risk factors for both ictal (ICA) and post-convulsive central apnea (PCCA) and their relationship with potential seizure severity biomarkers (i. e., post-ictal generalized EEG suppression (PGES) and recurrence.Methods: Prospective, multi-center seizure monitoring study of autonomic, and breathing biomarkers of SUDEP in adults with intractable epilepsy and monitored seizures. Video EEG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 53 publications
4
105
2
1
Order By: Relevance
“…The number of patients with postictally reduced oxygen saturation is similar or rather low when compared with results of dedicated studies on the effect of seizures on breathing. Bateman et al demonstrated that pulse oximetry will show oxygen desaturations below 90% in 33.2% of all seizures, and such data was well demonstrated in several recent studies, pointing especially at GTCS that lead to a temporary decline in breathing efforts and reduced peripheral oxygenation [32][33][34][35][36][37][38][39]. Overall, postictal respiratory depression may be caused by multiple reasons not limited to anticonvulsive treatment [9].…”
Section: Discussionmentioning
confidence: 90%
“…The number of patients with postictally reduced oxygen saturation is similar or rather low when compared with results of dedicated studies on the effect of seizures on breathing. Bateman et al demonstrated that pulse oximetry will show oxygen desaturations below 90% in 33.2% of all seizures, and such data was well demonstrated in several recent studies, pointing especially at GTCS that lead to a temporary decline in breathing efforts and reduced peripheral oxygenation [32][33][34][35][36][37][38][39]. Overall, postictal respiratory depression may be caused by multiple reasons not limited to anticonvulsive treatment [9].…”
Section: Discussionmentioning
confidence: 90%
“…In our study, we found no effect of either class of drug on PCCA, suggesting that PCCA may have a higher threshold for prevention effects than ICA or else, the number of PCCA seizures was too small for an effect to be seen. A recent study with a larger number of seizures (558 in 218 patients) found that longer ICA duration was related to PCCA presence [27], and therefore, preventing ICA may have relevance in the prevention of PCCA.…”
Section: Discussionmentioning
confidence: 98%
“…We prospectively studied 476 seizures in 204 patients. Of these, 312 seizures were part of a study of ICA incidence [6]; 148 generalized clonic seizures (GCS) were reported in another partially overlapping study that analyzed ICA and PCCA incidences [27,28]. All were consented participants in the National Institute of Neurological Disorders and Stroke (NINDS) Center for SUDEP Research's Autonomic and Imaging Biomarkers of SUDEP multicenter project (U01-NS090407) and its precursor, the Prevention and Risk Identification of SUDEP Mortality (PRISM) Project (P20NS076965).…”
Section: Patients and Clinical Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of electroencephalography (EEG), oxygen saturation levels, thoracoabdominal excursions, and electro-cardiography (ECG) with epilepsy patients, central apneas occurred during generalized convulsive seizures and post-ictal periods [4]. In a larger cohort of patients with focal epilepsy, central apneas were reported during and after 37% of seizures [5]. In a heart-monitoring study of implantable loop recorders in epilepsy patients over 24 months, peri-ictal cardiac arrhythmias were observed.…”
Section: Introductionmentioning
confidence: 99%